Association of Antibiotic Utilization and Neurodevelopmental Outcomes among Extremely Low Gestational Age Neonates without Proven Sepsis or Necrotizing Enterocolitis - Ting, Joseph Y.; Synnes, Anne; Roberts, Ashley; Deshpandey, Akhil C.; Dow, Kimberly; Yang, Junmin; Lee, Kyong-Soon; Lee, Shoo K.; Shah, Prakesh S.; on behalf of the Canadian Neonatal Network and Canadian Neonatal Follow-Up Network (American Journal of Perinatology, 2018)
Objective The objective is to evaluate the association between antibiotic utilization and neurodevelopmental outcomes at 18 to 21 months' corrected age among extremely low gestational age neonates without culture-proven sepsis or necrotizing enterocolitis (NEC).Study Design We conducted a retrospective cohort study of infants born between April 2009 and September 2011 at <29 weeks' gestation and admitted to the neonatal intensive care units contributing data to the Canadian Neonatal Network. Multivariable analysis was performed to examine the primary composite outcome of death or significant neurodevelopmental impairment (sNDI) in infants with various antibiotic utilization rates (AURs).Result There were 1,373 infants who fulfilled our inclusion criteria. Compared with infants in the lowest AUR quartile (Q1), those in the highest quartile (Q4) had higher odds of death or sNDI (adjusted odds ratio [AOR] = 7.44; 95% confidence interval [CI]: 4.55, 12.2) and death (AOR = 39.3; 95% CI: 16.1, 95.9).Conclusion Our results indicate an association between high AUR and a composite outcome of death or adverse neurodevelopmental outcomes at 18 to 21 months' corrected age.
Keywords: extremely low gestational age; neonate; antibiotic; neurodevelopmental outcomes